2005
DOI: 10.1167/iovs.04-0260
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Prevalence of Myopia in Young Adults: A 13-Year Series of Population-Based Prevalence Surveys

Abstract: During the 13 years from 1990 to 2002, the prevalence of myopia significantly increased among the Israeli population. Although there was an association with the level of education, gender, ethnicity, and origin, the prevalence of myopia increased on an annual basis, independent of these factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
127
2
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(141 citation statements)
references
References 15 publications
(9 reference statements)
8
127
2
3
Order By: Relevance
“…[4][5][6] In Taiwan, the prevalence of myopia among 12-and 13-year-old children is among the highest in South-East Asia. 1,3,7 A trend toward increasing myopia among 7-18-year-old Taiwanese children was observed between 1983 and 2000.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] In Taiwan, the prevalence of myopia among 12-and 13-year-old children is among the highest in South-East Asia. 1,3,7 A trend toward increasing myopia among 7-18-year-old Taiwanese children was observed between 1983 and 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Uncorrected refractive error is a common cause of vision impairment in children,2 with myopia being the most frequently seen refractive error, especially in East and Southeast Asian countries,3 such as Singapore, Japan, South Korea, Hong Kong, Taiwan, and parts of mainland China 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15. Elsewhere in the world as in North America, Australia, Europe and Middle East, the prevalence of myopia is also on the rise but at a slower pace 16, 17, 18, 19. As a consequence, the prevalence of high myopia is also on the rise.…”
Section: Introductionmentioning
confidence: 99%
“…Upon computing the equivalent ophthalmic prescription from the Zernike polynomial using the method described in [35], it was found that lens 5 had an equivalent prescription of -12.4332 sphere, -1.5244 cylinder at 162.40. This is far beyond the range of most human eyes, where only about 7% of myopes have high myopia ( < -6.0 Diopters) [4], leading to the conclusion that the lens itself is not representative of the population of human eyes with low vision. Additionally, it has been found that the larger the PSF (higher amount of sphere), the harder it is to generate an effective precompensation for display on conventional LCD panels.…”
Section: Key Findingsmentioning
confidence: 99%
“…PC-B '255 (3)(4)(5)(6)(7)(8)(9) where OPC-D is the "shifted and scaled" precompensated object. shows the result of simulating the retinal projection of the precompensated object.…”
Section: Opc-dmentioning
confidence: 99%
See 1 more Smart Citation